Christian Baptism - Piper, Otto (Scottish journal of theology, 1961)
Christian Baptism is rooted in the Baptism of John. The Dead Sea Scrolls and the excavation of Qumran have clearly shown that the Baptism practised by the Primitive Church had little in common with the daily washings of the Jewish sects. Our Baptism is an eschatological event. The foundational significance of the Baptist's ceremony performed in the Jordan river is emphasised by the fact that in all the four Gospels it is described as the beginning of Jesus' messianic ministry. The Gospel of John also informs us that Jesus shared in the Baptist's mission (John 3.22), even though He obviously left the actual ministration to His Disciples (John 4.2). Thus the Baptism which Jesus Himself commanded (Matt. 28.19–20), was the continuation of the eschatological ceremony started by the Baptist, though enriched by the reference to the messianic work of Jesus. The unique character of John's Baptism lies in the Word of God by which he is commanded to call Israel to repentance, to baptise them and to proclaim to them that his work is to usher in the establishment of God's final rule (the ‘Kingdom’) in this world. By accepting Baptism the Jewish people will be able to escape the final Judgment of God. The connexion in which the Word of God here stands with the eschatological events makes particularly plain what it means when God reveals Himself.